Cellulase Immobilization Using Reversible Soluble-Insoluble Polymer - MISRI GOZAN,; EDITA MARTINI,; DON-HEE PARK,; BAMBANG PRASETYA, (International Journal of Pharma and Bio Sciences, 2011)
Immobilization is considered to make the enzyme utilization more cost efficient. Cellulase should be in soluble form to attack the insoluble cellulose as insoluble enzyme is favourable for recycling. Stimuli responsive polymer is a polymer which can change its form reversibly due to stimulus (temperature or pH). N-succinyl chitosan (NSC) is one of smart polymers which is commonly used as a drug carrier, to dress wounds and to make cosmetic materials. In this experiment, NSC was made from 1 gm of chitosan mixed with 0.5 gm of succynil anhydride in 40 mL of dimethylsulfoxide (DMSO) and incubated for 18 – 24 hours at 60oC. The reusability percentage was 87 and it retained its activity at 180 U/mL. Optimum pH for NSC preparation was achieved at pH 4 – 5. A 5 mg EDCCl amount was used for 5 mL mixture to conjugate the NSC with cellulose. It showed its highest activity in terms of reducing sugar production as much as 2.85 mg/mL.